Privacy Preserving Image Transmission Using Random Pattern Mosaic Images Steganography - Survey - Kachhiya, Dhruval; Upadhayay, Keyur N; Bhatt, Tejaskumar P (International Journal of Computer Sciences and Engineering, 2025)
In today’s digital world, privacy concerns for data over the internet have increased. In many communications we transmit digital images and these images contain confidential information. Making is vulnerable towards unauthorized personals attacking the image and leaking our information which demands higher privacy. So, there are a number of methods available for achieving this privacy, one of them being Steganography. This make use of Mosaic image creation which has two distinct techniques, DWT (Discrete wavelet Transform) and DCT (Discrete Cosine Transform). The cover image is arbitrarily selected and uses of this image to hiding of the secret image. Secret image and cover image is split into tiny fragments called tile image and target block respectively. A secret image hiding scheme is proposed with new security features. This scheme utilizes the mosaic images, which is created from the secret and target images. A mosaic image is similar to that of the target image. The secret image fragments are hidden in the target image by performing appropriate color transformations. In these paper we are describe different types of watermarking techniques and differentiate using advantage and disadvantages for future research direction